Fourth industrial revolution model in the context of basic education in the Davao Region, Philippines - A. Diquito, Tomas Jr; Magallon, Jr., Silverio V. (International Journal of Evaluation and Research in Education (IJERE), 2025)
The Philippines is among the developing countries in the world which significantly affected by the technological advancement brought about by the fourth industrial revolution (4IR). Advancing the country’s manpower in the modern world requires preparedness for technological advancements. Thus, this study proposes a model in the context of basic education to better equip learners with modern approaches to education. The use of quantitative research design and factor analyses (both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA)) was carried out. A total of 550 teachers participated in the study, with 250 in EFA and 300 in CFA. The used of data reduction technique in EFA and model fit indices measures in CFA were used in the analyses. The results revealed three crucial dimensions in advancing education in the 4IR, these are: i) protection using cybersecurity; ii) use of simulation in teaching; and iii) school data management and analytics. Based on these findings, a model in basic education was developed to boost the Davao Region, Philippines’ preparedness to embrace technological advancement in the modern world. Moreover, the findings of this study can also serve as baseline data for other countries with similar profiles to the Philippines on how to approach education in 4IR.